Analysis of Intermittent Measurement for KF-based SLAM - Nur Aqilah, Othman; Hamzah, Ahmad; Saifudin, Razali (2013)
This paper investigates the impact of intermittent measurement to the Simultaneous Localization and Mapping (SLAM) of a mobile robot. Intermittent measurement is a condition when the mobile robot lost its measurement data during observations due to sensor failure or imperfection of the system. SLAM is an estimation process that requires measurement data recursively for data update. The analysis focused on the effect of intermittent measurement on the position estimation and state error covariance during intermittent and after intermittent occurred. From the analysis, it can be concluded that intermittent measurement may lead to incorrect estimation of robot pose and its error covariance.